COMPUTER MODELLING OF THE CROSS-COUNTRY GAS PIPELINE SECTION - Nikita V. KUDINOV; Anna A. BOLDYREVA (Advanced Engineering Research, 2010)
Algorithmic and program implementation of modeling of the technological objects distributed systems is considered. The technology of hierarchic class structure development agreed upon multiple inheritance in C++ is offered for software authoring. Research of the given software tool when modeling standard simulation models is described.